Effect of Arginine Supplementation on Vasodilation and Muscular Performance in Young Men: A Randomized, Double-Blind, Crossover Study - De Moraes-Ferrari, G (HUMAN KINETICS PUBL INC, 2026)
This study aimed to evaluate the effects of short-term oral L-arginine (ARG) supplementation on vascular parameters, nitric oxide (NO) concentration, and muscular performance during upper limb resistance exercise in healthy young men. A randomized, doubleblind, crossover design was used with 16 recreationally trained men. Participants ingested ARG (3.2-9.6 g/day) or placebo for 4 days, separated by a 14-day washout. On the fourth day, they completed three sets of biceps curls at 65% of one-repetition maximum to concentric failure. Primary outcomes included total repetitions performed and fatigue ratio. Secondary outcomes comprised brachial artery diameter, peak systolic velocity, blood flow (velocity-time integral), vascular resistance index, plasma NO, and blood lactate concentrations. No significant differences were observed between ARG and placebo in muscular endurance (total repetitions, p = .305), volume load, or fatigue ratio. Plasma NO levels did not differ between conditions (p = .522). Although brachial artery diameter significantly increased 1-min postexercise in the ARG condition compared with placebo (p = .023), no differences were found for velocity-time integral, peak systolic velocity, resistance index, or blood pressure. Blood lactate concentrations rose after exercise in both groups, with a nonsignificant value in the ARG condition (p = .09 at 9-min postexercise). Short-term oral ARG supplementation did not enhance muscular endurance, systemic NO concentration, or vascular function during upper limb resistance exercise in healthy young men. Although a minor increase in brachial artery dilation was observed shortly after exercise, the effect was transient and insufficient to support meaningful ergogenic benefits.